2017
DOI: 10.1002/jrs.5107
|View full text |Cite
|
Sign up to set email alerts
|

The first use of portable Raman instrumentation for the in situ study of prehistoric rock paintings in Patagonian sites

Abstract: Portable Raman spectroscopy is applied for the first time on rock art paintings from hunter‐gatherers in three different provinces in Patagonia, Argentina (Neuquén, Río Negro and Chubut). Selected archaeological sites were examined, revealing the local ‘palette’ of the native population and, if possible, the technology used. Moreover, alteration products were investigated to obtain valuable information for a better conservation and preservation of these magnificent rock art paintings. During a single research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 65 publications
(121 reference statements)
1
22
0
1
Order By: Relevance
“…literature describing the use of portable Raman spectrometers [11,[17][18] in field studies with excellent results on the characterization of pigments, crusts and substrata.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…literature describing the use of portable Raman spectrometers [11,[17][18] in field studies with excellent results on the characterization of pigments, crusts and substrata.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In fact, there are few studies dedicated to the in situ analysis of degradation and taphonomic processes of rock art pigments and rock supports [28][29][30]. portable Raman spectrometer to analyse rock art paintings under extreme conditions in Patagonia (Argentina) where a more detailed description of the literature and the possibilities of Raman spectroscopy on rock art paintings is given [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…During a single research campaign, 16 shelters and one cave were investigated, which makes this study as one of the most condensed expeditions on measuring rock art paintings. They also evaluated the use of their portable Raman instrument under the extreme conditions of Patagonia . In Tascon et al's Determination of materials and techniques involved in the mural paintings of San Miguel Church, Argentina , they concluded that the use of complementary and microdestructive spectroscopic methodologies is a very useful tool to determine not only the materiality but also the execution technique of the painting in order to assess, in an interdisciplinary approach, the future restoration and preservation strategies …”
Section: Art and Archaeologymentioning
confidence: 99%
“…No âmbito da Ciência do Patrimônio, a técnica vem sendo aplicada em estudos variados. No caso de pinturas rupestres diversas publicações podem ser encontradas na literatura (DARCHUK et al, 2010;DE FARIA e LOPES, 2011;DE FARIA e MENEZES, 2011;ROUSAKI et al, 2015;SEPULVEDA et al, 2015;MOYA et al, 2016;TASCON et al, 2016;GHECO et al, 2017;ROUSAKI et al, 2017;TRONCOSO et al, 2017;MORILLAS et al, 2018) sendo que o objetivo mais frequente é a identificação de pigmentos usados na produção das pinturas (DARCHUK et al, 2010;ROUSAKI et al, 2015;TASCON et al, 2016;GHECO et al, 2017;ROUSAKI et al, 2017) com a perspectiva de ampliar o conhecimento sobre práticas e técnicas dominadas por diferentes culturas ou, ainda, compreender melhor os processos associados à deterioração dos pictogramas (DE FARIA e MENEZES, 2011;FARIAS FILHO et al, 2017;MORILLAS et al, 2018). Tais análises foram usualmente feitas em amostras coletadas das pinturas seguindo procedimentos aprovados pelos órgãos de proteção ao patrimônio cultural, mas há uma publicação na qual os espectros foram obtidos in situ com o uso de instrumento portátil com duas radiações de excitação (532 nm and 785 nm) (ROUSAKI et al, 2017); nesse artigo são destacadas algumas das dificuldades encontradas no uso em campo desse tipo de instrumento.…”
Section: Aplicações Em Estudos De Bens Culturais -América Do Sulunclassified